FENOLOGI PERTUMBUHAN VEGETATIF DAN GENERATIF TANAMAN DUKU VARIETAS KUMPEH PADA BERBAGAI UMUR (The Phenology of Vegetative and Generative Growth of Duku Kumpeh Varieties at Various Age) - . Lizawati; Budiyati Ichwan; . Gusniwati; . Neliyati; Muhammad Zuhdi (Bioplantae, 2013)
The objective pf this research was to determine the phenology of vegetative and generative growth of duku plant variety kumpeh at different ages. The treatment was design in randomized block design (RBD) with duku plant age duku as a treatment. The treatments tested were analysis : LA=Age plants less than 25 years; plants LB=Age 25-50 years, and LC=Age 50 years and older plants. On the obtained results, that theair temperature has a positive correlation to the length of shoots, shoots diameter and number of leaves at different plant age duku. Poster for the end of all plant life duku happened in September but there is a difference between the starting time and peak Poster. Flowering in plants duku occurredin the village of Karang Cityin early Octoberis the end of the dry season or the beginning of the rainy season. Duku fruit that reaches fruit set can beharvestedat 125 days after anthesis. Duku plants aged >50 produce fruit that tastes sweeter, with asugarcontent of 18.93% and 0.36% acid levels. Key words :Anthesis, Lansium domesticum, trubus